CFRP strips for enhancing flexural performance of RC beams by SNSM strengthening technique - Hosen, Md Akter; Jumaat, Mohd Zamin; Alengaram, Ubagaram Johnson; Ramli Sulong, Nor Hafizah (Elsevier, 2018)
Side Near Surface Mounted (SNSM) strengthening technique is among the latest technique introduced recently. In this paper, SNSM carbon fiber reinforced polymer (CFRP) strips strengthening technique is proposed for enhancing the flexural performance of reinforced concrete (RC) beams. A total of seven RC beam specimens were tested: one un-strengthened control specimen, and six specimens strengthened by SNSM-CFRP strips. All beam specimens were tested under four-point bending. Analytical prediction methods were used to verify the experimental results. The load, mid-span, deflection, and strains data were recorded until failure of the specimens. The ductility, stiffness, and energy absorption capacity of the strengthened specimens by CFRP strips were enhanced due to SNSM technique. The results also showed that the SNSM-CFRP strips strengthening technique significantly enhanced the first cracking, yield, and ultimate load capacities up to 153%, 108%, and 147% respectively, compared with that of the control beam. Further, the comparison between the experimental and predicted values shows good agreement.